Practical Biology activities: an Investigative Teaching Sequence about the Cell Cycle (Research, Society and Development, 2020)
The aim of this study was to develop and to analyze the use of an Investigative Teaching Sequence (ITS) about the cell cycle (mitosis), composed by a didactic model and by a practical class with Allium cepa L. with students from two public schools and from a particular one in Floriano (PI). Through the answers to the questioning of ITS, it was found that the students had disconnected and fragmented knowledge about the content of the cell cycle. The ITS application modified the attitude of the students of the three schools, which became more participative among themselves and with the teacher, corroborating with the data obtained from the comparison of pre and post-test questionnaires. The applied active methodologies were satisfactory and had great acceptance by the students. Therefore, it was found that the use of ITS facilitated the understanding of the dynamics surrounding the cell cycle and its implications for the constitution of living beings, minimizing the distance between theory and practice.